Characterization and phylogenomic analysis of Breznakiella homolactica gen. nov. sp. nov. indicate that termite gut treponemes evolved from non‐acetogenic spirochetes in cockroaches. (17th June 2021) - Song, Yulin; Hervé, Vincent; Radek, Renate; Pfeiffer, Fabienne; Zheng, Hao; Brune, Andreas
Summary: Spirochetes of the genus Treponema are surprisingly abundant in termite guts, where they play an important role in reductive acetogenesis. Although they occur in all termites investigated, their evolutionary origin is obscure. Here, we isolated the first representative of 'termite gut treponemes' from cockroaches, the closest relatives of termites. Phylogenomic analysis revealed that Breznakiella homolactica gen. nov. sp. nov. represents the most basal lineage of the highly diverse 'termite cluster I', a deep‐branching sister group of Treponemataceae (fam. ' Termitinemataceae ') that was present already in the cockroach ancestor of termites and subsequently coevolved with its host. Breznakiella homolactica is obligately anaerobic and catalyses the homolactic fermentation of both hexoses and pentoses. Resting cells produced acetate in the presence of oxygen. Genome analysis revealed the presence of pyruvate oxidase and catalase, and a cryptic potential for the formation of acetate, ethanol, formate, CO2 and H2 ‐ the fermentation products of termite gut isolates. Genes encoding key enzymes of reductive acetogenesis, however, are absent, confirming the hypothesis that the ancestral metabolism of the cluster was fermentative, and that the capacity for acetogenesis from H2 plus CO2 ‐ the most intriguing property among termite gut treponemes ‐ was acquired by lateral gene transfer.